Alexander Allan Shand and Parr's Bank: Roles as a director from 1909 to 1918 - Eiji Hotori (The European Association for Banking and Financial History (EABH), 2023)
In this article, I use documents obtained from the NatWest Group archives to examine the work of Alexander Shand as a director of Parr's Bank during the period 1909-1918. A Scottish banker, Alexander Shand was recruited by the Japanese government early in his career to instruct Japanese bureaucrats on the establishment of a modern banking system. Following a conflict with the Japanese government in 1877, Shand returned to the United Kingdom, where he used his connections within the British bankers' network to obtain a position with Alliance Bank, commencing in 1878. In 1892, Alliance Bank merged with Parr's Bank, and Shand was eventually appointed to the board in 1909, where he remained until Parr's Bank merged with Westminster Bank in 1918. Shand was not only keen to maintain discipline regarding insider lending, but also played an important role in underwriting bonds issued in Japan and China. In addition, Shand dealt with difficult issues related to the bank's participation in bailout plans and tax-related matters. This article confirms Shand's industrious and conservative attitude as a director of a British bank, as well as his sound management principles in the early 20th century.
Keywords: N23; N83; N93; 330; financial history; UK-Japan relationship; British bank